The difficulty with responding to policy changes for HIV and infant feeding in Malawi - de Paoli Marina; Sundby Johanne; Chinkonde Jacqueline R; Thorsen Viva C (BMC, 2010)
Abstract Background When and how to wean breastfed infants exposed to HIV infection has provoked extensive debate, particularly in low-income countries where safe alternatives to breastfeeding are rarely available. Although there is global consensus on optimal infant-feeding practices in the form of guidelines, practices are sub-optimal in much of sub-Saharan Africa. Policy-makers and health workers face many challenges in adapting and implementing these guidelines. Methods This paper is based on in-depth interviews with five policy-makers and 11 providers of interventions to prevent mother-to-child transmission (PMTCT) of HIV, participant observations during clinic sessions and site visits. Results The difficulties with adapting the global infant-feeding guidelines in Malawi have affected the provision of services. There was a lack of consensus on HIV and infant-feeding at all levels and general confusion about the 2006 guidelines, particularly those recommending continued breastfeeding after six months if replacement feeding is not acceptable, feasible, affordable, sustainable and safe. Health workers found it particularly difficult to advise women to continue breastfeeding after six months. They worried that they would lose the trust of the PMTCT clients and the population at large, and they feared that continued breastfeeding was unsafe. Optimal support for HIV-infected women was noted in programmes where health workers were multi-skilled; coordinated their efforts and had functional, multidisciplinary task forces and engaged communities. The recent 2009 recommendations are the first to support antiretroviral (ARV) use by mothers or children during breastfeeding. Besides promoting maternal health and providing protection against HIV infection in children, the new Rapid Advice has the potential to resolve the difficulties and confusion experienced by health workers in Malawi. Conclusions The process of integrating new evidence into institutionalised actions takes time. The challenge of keeping programmes, and especially health workers, up-to-standard is a dynamic process. Effective programmes require more than basic resources. Along with up-to-date information, health workers need contextualized, easy-to-follow guidelines in order to effectively provide services. They also require supportive supervision during the processes of change. Policy-makers should ensure that consensus is carefully considered and that comprehensive perspectives are incorporated when adapting the global guidelines.